Dynamic charge transport in pentacene and zinc oxide thin-film transistors: Dark and UV illumination conditions - Mansouri, S.; Bourguiga, R.; Al-Ghamdi, A. A.; Al-Hazmi, Faten; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
The electronic charge transport of thin film transistors (TFTs) based on pentacene and zinc oxide semiconductors was studied. A mathematical model is presented based on the variable range hopping (VRH) transport theory. Using the VRH model, the expression of source drain current is established under dark and under UV illumination (365 nm) in linear regime for drain bias V-D = 2 V and 2 V, when we used pentacene and zinc oxide, respectively, at 300 K. All electrical key parameters of TFTs based on pentacene and zinc oxide were extracted. A good agreement between theoretical model and experimental measurement, transfer characteristics was obtained under dark and UV illumination conditions. Finally, we give a simple small-signal equivalent circuit to the organic and inorganic thin film transistor. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Organic-inorganic TFTs; VRH model; Dynamic charge transport model; Effect of UV illumination